2014
DOI: 10.1111/maec.12199
|View full text |Cite
|
Sign up to set email alerts
|

The rise of Laminaria ochroleuca in the Western English Channel (UK) and comparisons with its competitor and assemblage dominant Laminaria hyperborea

Abstract: The distribution of species is shifting in response to recent climate change. Changes in the abundance and distributions of habitat-forming species can have knock-on effects on community structure, biodiversity patterns and ecological processes. We empirically examined temporal changes in the abundance of the warm-water kelp Laminaria ochroleuca at its poleward range edge in the Western English Channel. Resurveys of historical sites indicated that the abundance of L. ochroleuca has increased significantly in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 81 publications
4
71
1
Order By: Relevance
“…For example, a comparison of epibionts attached to farmed U. pinnatifida and S. latissima sporophytes showed that S. latissima generally exhibits higher levels of biofouling (Peteiro and Freire, 2013). L. ochroleuca is also known to produce antifoulants, and the surfaces of the stipe and lamina are generally less fouled by epibionts than other kelps including L. hyperborea (Smale et al, 2015), L. digitata (Blight and Thompson, 2008) and S. latissima (this study). Even so, epiphytic loading and the richness and cover of epibionts on the stipe and lamina habitat of L. ochroleuca were still comparable to or greater than that of U. pinnatifida.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, a comparison of epibionts attached to farmed U. pinnatifida and S. latissima sporophytes showed that S. latissima generally exhibits higher levels of biofouling (Peteiro and Freire, 2013). L. ochroleuca is also known to produce antifoulants, and the surfaces of the stipe and lamina are generally less fouled by epibionts than other kelps including L. hyperborea (Smale et al, 2015), L. digitata (Blight and Thompson, 2008) and S. latissima (this study). Even so, epiphytic loading and the richness and cover of epibionts on the stipe and lamina habitat of L. ochroleuca were still comparable to or greater than that of U. pinnatifida.…”
Section: Discussionmentioning
confidence: 99%
“…The shift from long-lived perennial species to short-lived annual species represents a shift in habitat structure from temporally-stable to 'boom and bust' and is likely to have major implications for primary production and biogenic habitat provision. However, the situation is complicated by the proliferation of the 'warm' water kelp L. ochroleuca at its poleward range edge in southwest UK (Smale et al, 2015). On wave-exposed open coastlines L. ochroleuca may support less diverse and abundant assemblages than its cool-water competitor L. hyperborea (Smale et al, 2015; Teagle unpublished data) but in more sheltered locations L. ochroleuca seemingly provides relatively stable and complex biogenic habitat that supports comparatively diverse and abundant epibiont assemblages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kelp forest declines have now been documented in many regions in response to a variety of stressors (18,(31)(32)(33)(34)(35), but kelp abundances have been stable or increasing in other areas (17,36,37). Here, we amass a global database of kelp abundances to provide a comprehensive picture of kelp forest change.…”
Section: Significancementioning
confidence: 99%